RELASI PENDIDIK DAN PESERTA DIDIK DALAM PEMBELAJARAN AGAMA BERBASIS DIGITAL: KAJIAN LITERATUR TENTANG INTERAKSI DAI DAN MAD'U - Jami'atus Sholeha; Intan Trine Chodija (STKIP Pesisir Selatan, 2026)
This study examines the transformation of religious education in the digital space, focusing on changes in educator authority, emotional approaches in interactions, and psychosocial impacts on learners. This research uses a qualitative approach with a literature review method on various relevant academic literatures. The results show three main findings. First, religious educational authority has shifted from formal institutions to individuals active on social media, where recognition is based on communication skills and online visibility. Second, the learning process heavily prioritizes emotional approaches through storytelling techniques and expressions of empathy to build closeness. However, this approach carries the risk of performativity that can obscure the depth of religious teachings for the sake of content popularity. Third, digital interactions have a real psychosocial impact on learners' daily behaviors, but risk triggering confirmation bias, rigid religious attitudes, and psychological pressure. This study concludes that digital religious education requires ethical responsibility from educators and a reflective critical attitude from learners so that the understanding of religious values remains deep and healthy.